An ISHLT consensus statement on strategies to prevent and manage hemocompatibility related adverse events in patients with a durable, continuous-flow ventricular assist device - Hollis, Ian B.; Jennings, Douglas L.; Krim, Selim; Ton, Van-Khue; Ducharme, Anique; Cowger, Jennifer; Looby, Mary; Eulert-Green, J. J.; Bansal, Neha; Horn, Ed; Byku, Mirnela; Katz, Jason; et al. (The journal of heart and lung transplantation, 2024)
Life expectancy of patients with a durable, continuous-flow left ventricular assist device (CF-LVAD) continues to increase. Despite significant improvements in the delivery of care for patients with these devices, hemocompatability-related adverse events (HRAEs) are still a concern and contribute to significant morbility and mortality when they occur. As such, dissemination of current best evidence and practices is of critical importance. This ISHLT Consensus Statement is a summative assessment of the current literature on prevention and management of HRAEs through optimal management of oral anticoagulant and antiplatelet medications, parenteral anticoagulant medications, management of patients at high risk for HRAEs and those experiencing thrombotic or bleeding events, and device management outside of antithrombotic medications. This document is intended to assist clinicians caring for patients with a CF-LVAD provide the best care possible with respect to prevention and management of these events.